Melanin Pigment in Plants: Current Knowledge and Future Perspectives - Glagoleva, Anastasiia Y.; Shoeva, Olesya Y.; Khlestkina, Elena K. (Frontiers in Plant Science, 2020)
The word “melanin” refers to a group of high molecular weight, black, and brown pigments formed through the oxidation and polymerization of phenolic compounds. This pigment is present in all kingdoms of living organisms, but it remains the most enigmatic pigment in plants. The poor solubility of melanin in particular solvents and its complex polymeric nature significantly constrain its study. Plant melanin synthesis is mostly associated with the enzymatic browning reaction that occurs in wounded plant tissues. This reaction occurs when, due to the disruption of cellular compartmentation, the chloroplast-located polyphenol oxidases (PPOs) release from the chloroplast and interact with their vacuolar substrates to produce o-quinones, which in turn polymerize to melanin. Furthermore, the presence of melanin in intact seed tissues has been demonstrated by diagnostic physicochemical tests. Unlike the well-studied enzymatic browning reaction, little is known about how melanin is formed in seeds. Recent data have shown that it is a tightly controlled genetic process that involves many genes, among which the genes encoding PPOs might be key. The present article aims to provide an overview of the current knowledge on melanin in plants and to discuss future perspectives on its study in light of recent findings.